Multi-anti-counterfeiting flexible label and preparation method thereof
By preparing multiple anti-counterfeiting flexible labels, using fluorescent adhesives and invisible identification layers, the problem of lack of anti-counterfeiting marks for the goods after the label is removed is solved, and the traceability and multiple anti-counterfeiting functions of the goods are realized.
Patent Information
- Application Number
- CN202510033007.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-09
AI Technical Summary
After the existing label is removed from the product, it usually leaves no anti-counterfeiting marks or traces, making it difficult to trace the authenticity of the product.
Using the preparation method of multiple anti-counterfeiting flexible labels, acrylic modified aqueous polyurethane adhesive is obtained by mixing aromatic polyester polyol, aliphatic isocyanate, modified acrylic monomer and additives, and adding fluorescent powder to form fluorescent glue. Adhesive. The adhesive is slightly concavely coated on gracin paper to cure, forming a glue layer, and curing it on other levels of the label to ultimately form a complete multiple anti-counterfeiting flexible label.
After the label is removed from the product, the glue layer remains on the product, and it is imaged after being exposed to purple light to achieve anti-counterfeiting function. At the same time, invisible logos and multi-layer structures improve the anti-counterfeiting effect of the label and ensure that the authenticity of the product is traceable.
Smart Images

Figure CN119445970A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of label preparation, and in particular to a multiple anti-counterfeiting flexible label and a preparation method thereof. Background Art
[0002] With the development of science and technology and the intensification of market competition, the issue of product anti-counterfeiting has become increasingly important. Especially today when the crackdown on counterfeit products is constantly increasing, anti-counterfeiting technology has become a research focus in all walks of life. As a common anti-counterfeiting measure, product anti-counterfeiting labels are widely used in various consumer products, including food, cosmetics, pharmaceutical products, electronic products, etc. At present, most of the common anti-counterfeiting labels on the market rely on the material, printing process, optical properties, etc. of the label itself to achieve anti-counterfeiting functions, such as QR codes, laser etching, microtext, holograms, invisible inks and other technical means.
[0003] Existing anti-counterfeiting methods for labels are relatively simple. Most anti-counterfeiting technologies only identify the authenticity of goods through external features such as patterns and colors. Most of the current labels are attached to the surface of the goods through adhesives or glue. These labels can be easily peeled off when in use, and after the label is peeled off, there are usually no anti-counterfeiting marks or traces left on the goods. Therefore, once the label is removed, the authenticity of the goods is difficult to trace.
[0004] Therefore, a multiple anti-counterfeiting flexible label and a preparation method thereof are proposed to solve the problem that after the label is peeled off, no anti-counterfeiting mark or trace is usually left on the commodity. Summary of the invention
[0005] The object of the present invention is to provide a multiple anti-counterfeiting flexible label and a preparation method thereof, so as to solve the problem that after the label is peeled off, usually no anti-counterfeiting mark or trace is left on the commodity.
[0006] To achieve this object, the present invention adopts the following technical solutions: A method for preparing a multiple anti-counterfeiting flexible label comprises the following steps: S1, mixing aromatic polyester polyol, aliphatic isocyanate, modified acrylate monomer and additives to obtain acrylic acid modified waterborne polyurethane adhesive, and then adding fluorescent powder to mix to obtain fluorescent adhesive; S2, applying the obtained fluorescent adhesive micro-concave onto glassine paper and curing it to form an adhesive layer to obtain an initial substrate; S3, preparing a white curing liquid and a black curing liquid, first coating the white curing liquid on the initial substrate for curing, then coating the black curing liquid, and after curing, obtaining a final substrate; S4, preparing invisible mark forming liquid, first curing the invisible mark forming liquid on the final substrate, and then coating the modified acrylate liquid, and obtaining a complete label after curing.
[0007] The acrylic acid modified waterborne polyurethane adhesive is obtained according to the following steps: Step 1: Adding aromatic polyester polyol and aliphatic isocyanate into a reaction kettle for stirring, after stirring for 2 hours, at a stirring speed of 200 rpm and a stirring temperature of 80±5°C, a preliminary mixture is obtained, and the -NCO groups in the preliminary mixture are fully reacted to form a polyurethane prepolymer; Step 2: gradually add modified acrylate monomer to the preliminary mixture, and then stir for 1 hour at a stirring speed of 300 rpm and a stirring temperature of 70±5°C, at which time the acrylate monomer is grafted onto the polyurethane chain to form an acrylic modified polyurethane prepolymer; Step 3: gradually adding a chain extender to the acrylic modified polyurethane prepolymer, and stirring for 30 minutes, at a stirring speed of 300 rpm and a stirring temperature of 50±5°C to obtain a chain extension mixture, and after no obvious gel or particle precipitation in the chain extension mixture, adding deionized water for stirring, stirring for 30 minutes, at a stirring speed of 400 rpm and a stirring temperature of 50±5°C, and after the mixture of the chain extension mixture and the deionized water is a milky white or translucent uniform emulsion, and no obvious stratification or large particles exist, a preliminary emulsion is obtained; Step 4: After the preliminary emulsion is cooled to room temperature, an auxiliary agent is added and stirred for 15 minutes at a stirring speed of 300 rpm. After the stirring is completed, triethylamine is added to adjust the pH value of the mixture of the preliminary emulsion and the auxiliary agent to 7-8 to obtain an acrylic acid-modified waterborne polyurethane adhesive; The theoretical viscosity calculation formula of the acrylic acid modified waterborne polyurethane adhesive is: Where: is the viscosity of acrylic modified waterborne polyurethane adhesive; is an empirical constant; is the density of acrylic modified waterborne polyurethane adhesive; is the glass transition temperature of acrylic acid modified waterborne polyurethane adhesive; is the operating temperature; is the average molecular weight of acrylic acid modified waterborne polyurethane adhesive; The fluorescent adhesive is obtained according to the following steps: The fluorescent powder and the acrylic modified waterborne polyurethane adhesive were stirred and mixed for 15 minutes at a stirring speed of 400 rpm; Obtaining the actual viscosity of the acrylic modified waterborne polyurethane adhesive , and compare and , determine whether the water content of the acrylic modified waterborne polyurethane adhesive needs to be increased or decreased. If the actual viscosity of the acrylic modified waterborne polyurethane adhesive is Greater than the theoretical viscosity of acrylic modified waterborne polyurethane adhesive Then add deionized water to dilute it and reduce the viscosity. On the contrary, if the actual viscosity of the acrylic modified waterborne polyurethane adhesive is obtained Less than the theoretical viscosity of acrylic modified waterborne polyurethane adhesive Continue stirring to reduce the water content and increase the viscosity.
[0008] The aromatic polyester polyol may be any one of polytrimethylene terephthalate, polyethylene terephthalate, and polyethylene adipate terephthalate; The aliphatic isocyanate may be any one of isophorone diisocyanate, hexamethylene diisocyanate, and tetramethylene diisocyanate; The modified acrylate monomer may be any one of hydroxyethyl acrylate, hydroxypropyl methacrylate, and butyl methacrylate; The auxiliary agents include stabilizers, tackifiers and antioxidants.
[0009] In the preparation of the modified acrylate monomer, the proportions of aromatic polyester polyol, aliphatic isocyanate, modified acrylate monomer, modified acrylate monomer, deionized water, chain extender and auxiliary agent are 40% to 50%, 20% to 25%, 10% to 15%, 15% to 20%, 0.5% to 1.5% and 5% to 10% respectively; Among them, the additives include stabilizers, tackifiers and antioxidants; The proportion of stabilizers is 0.1%~0.5%, the proportion of tackifiers is 1%~5%, and the proportion of antioxidants is 0.1%~0.3%; The fluorescent powder and acrylic modified waterborne polyurethane adhesive account for 8% to 13% and 87% to 92% of the fluorescent adhesive, respectively.
[0010] The initial substrate is obtained according to the following steps: The first step: preparing a coating mold with a micro-concave structure, and coating a release layer on the coating mold so that the release layer covers the micro-concave structure, wherein the coating mold is provided with a plurality of square grooves with equal spacing corresponding to its rubbing surface, and two adjacent square grooves enclose one micro-concave structure; Step 2: Apply the fluorescent adhesive to the coating mold and fill the micro-concave structure with the fluorescent adhesive; Step 3: The fluorescent adhesive is evenly printed on the glassine paper through a coating mold. The release layer coating can completely transfer the fluorescent adhesive from the micro-concave structure to the glassine paper. After the coating is completed, the glassine paper is subjected to six-stage thermal curing. After the fluorescent adhesive forms an adhesive layer on the glassine paper, the initial substrate is finally obtained, wherein bumps are formed on the adhesive surface of the adhesive layer on the initial substrate corresponding to the square grooves.
[0011] The depth of the micro-concave structure on the coating mold is 20-30 μm, the width is 50-100 μm, and the groove spacing is 100-150 μm; The coating thickness of the fluorescent adhesive is 25±5 μm; The six curing temperatures of the six-stage thermal curing are 75±5°C, 85±5°C, 95±5°C, 115±5°C, 110±5°C, and 90±5°C, respectively; the six curing times of the six-stage thermal curing are 5-10 minutes, 10-15 minutes, 10-20 minutes, 5-10 minutes, 5-10 minutes, and 10-15 minutes, respectively.
[0012] The final substrate is obtained according to the following steps: The first step is to apply a white curing liquid composed of a modified acrylic ester liquid and a white pigment on the adhesive layer on the initial substrate, and then thermally cure the white curing liquid to form a white curing layer on the adhesive layer after the white curing liquid is cured; Step 2: coating a black curing liquid composed of a modified acrylic ester liquid and a black pigment on the white curing layer, and then thermally curing the black curing liquid. After the black curing liquid is cured to form a black curing layer, the final substrate is obtained.
[0013] The complete label is obtained according to the following steps: The first step: coating the invisible logo forming liquid composed of modified acrylic ester liquid and fluorescent powder on the invisible logo mold, and transferring the invisible logo forming liquid to the surface of the final substrate through the invisible logo mold, and then curing the invisible logo forming liquid on the surface of the final substrate through thermal curing to form an invisible logo layer; Step 2: Apply the modified acrylic ester liquid on the invisible logo layer, and then cure it by heat curing. When a transparent cured layer is formed on the invisible logo layer, a complete label is obtained.
[0014] The invisible mark forming liquid is prepared by mixing modified acrylic ester liquid and fluorescent powder, the mixing time is 10 to 20 minutes, and the stirring speed is 200 to 600 rpm; Among them, the proportions of modified acrylate liquid and fluorescent powder in the invisible marking forming liquid are 92% to 87% and 8% to 13% respectively.
[0015] A multiple anti-counterfeiting flexible label is made by the method described above, and comprises glassine paper, a glue layer, a white solidified layer, a black solidified layer, an invisible marking layer, and a transparent solidified layer connected in sequence from bottom to top.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The preparation method of the multiple anti-counterfeiting flexible label is obtained by curing the fluorescent adhesive and setting the adhesive layer on the initial substrate, so that after the label is peeled off from the commodity, the fluorescent adhesive remains on the commodity, and the residual fluorescent adhesive is imaged after being irradiated with ultraviolet light to achieve the anti-counterfeiting function, which solves the problem that no anti-counterfeiting mark is left on the commodity after the label is peeled off from the commodity. Therefore, the present invention can leave an anti-counterfeiting mark on the commodity after the label is peeled off from the commodity.
[0017] 2. The preparation method of the multiple anti-counterfeiting flexible label can enable the label to achieve multiple anti-counterfeiting functions by setting an invisible mark and cooperating with the set adhesive layer. The invisible mark on the visible surface and the inner adhesive layer cooperate to effectively improve the anti-counterfeiting effect of the label. Therefore, the present invention has multiple anti-counterfeiting functions.
[0018] 3. The preparation method of the multiple anti-counterfeiting flexible label can effectively improve the viscosity of the fluorescent adhesive by forming an acrylic modified water-based polyurethane adhesive from aromatic polyester polyols, aliphatic isocyanates, modified acrylic ester monomers and additives. In addition, with the cooperation of the finely arranged micro-concave structure on the coating mold, the fluorescent adhesive can be coated on the glassine paper by micro-concave coating, so that convex blocks are formed on the adhesive surface of the adhesive layer. The convex blocks allow more adhesive layer to remain on the label when it is peeled off from the product, thereby improving the imaging effect of ultraviolet light irradiation. Therefore, the present invention improves the imaging effect of fluorescent residue.
[0019] 4. The preparation method of the multiple anti-counterfeiting flexible label and the fluorescent adhesive prepared can not only make the residual adhesive layer on the product emit an obvious fluorescent display effect after being irradiated with ultraviolet light, but also make the residual adhesive layer on the product emit fluorescent imaging after being irradiated with ultraviolet light. Therefore, the present invention further improves the anti-counterfeiting effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0021] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.
[0022] Figure 1 is a flow chart of the method steps of the present invention; Figure 2 The present invention is a flow chart of the steps for preparing the acrylic acid modified waterborne polyurethane adhesive; Figure 3 is a flow chart of the steps for preparing the initial substrate in the present invention; Figure 4 It is a schematic diagram of the separation structure of the coating mold and the adhesive layer in the present invention; Figure 5 It is a schematic diagram of the top view of the structure of the glue layer in the present invention; Figure 6 is a flow chart of the steps for preparing the final substrate in the present invention; Figure 7 The figure is a flow chart of the steps for preparing a complete label in the present invention.
[0023] Illustrations: 1. Coating mold; 11. Square groove; 12. Rubbing surface; 2. Adhesive layer; 21. Adhesive surface; 22. Bump. DETAILED DESCRIPTION
[0024] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the description of the present invention, it should be understood that the terms "upper", "lower", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present invention. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally arranged component at the same time.
[0026] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0027] Embodiment 1: See also Figure 1 In this embodiment, a method for preparing a multiple anti-counterfeiting flexible label includes the following steps: S1, mixing aromatic polyester polyol, aliphatic isocyanate, modified acrylate monomer and auxiliary agent to obtain acrylic modified waterborne polyurethane adhesive, and then adding fluorescent powder to obtain fluorescent adhesive; S2, applying the obtained fluorescent adhesive to glassine paper with micro-concave coating to form adhesive layer 2, and then obtaining an initial substrate; S3, preparing white curing liquid and black curing liquid, first coating the white curing liquid on the initial substrate for curing, and then coating the black curing liquid, and obtaining the final substrate after curing; S4, preparing invisible mark forming liquid, first curing the invisible mark forming liquid on the final substrate, and then coating the modified acrylate liquid, and obtaining a complete label after curing.
[0028] The label prepared by the above method can be firmly adhered to the product under the action of the adhesive layer 2 after being pasted on the product. During the use of the label, the invisible mark formed by the invisible mark forming liquid can enable the label to play an anti-counterfeiting role, so that the label has an anti-counterfeiting function, and after the label is peeled off from the product, the adhesive layer 2 will remain on the product, and when purple light is irradiated on the remaining adhesive layer 2, the fluorescent powder in the adhesive layer 2 will emit a fluorescent prompt, and under the action of the remaining adhesive layer 2, it can be displayed on the product from which the label is peeled off, thereby forming an anti-counterfeiting label again. Under the action of the invisible mark and the fluorescent residue, the label has multiple anti-counterfeiting functions, which improves the anti-counterfeiting effect of the label, and when the adhesive layer 2 remaining on the product is removed, there will still be fluorescent residue at the adhesive part of the label, and when purple light is irradiated on the adhesive part of the label, there will still be an imaging effect, which further improves the anti-counterfeiting function of the label.
[0029] It should be noted that when the label is used, after the glassine paper is peeled off from the label, the label can be adhered to the product through the adhesive layer 2; the label can be marked by laser etching and used as a mark.
[0030] Embodiment 2: Basic content embodiment 1, the difference is: See also Figure 2-Figure 5The acrylic modified waterborne polyurethane adhesive in this embodiment is obtained according to the following steps: the first step: adding aromatic polyester polyol and aliphatic isocyanate into a reaction kettle for stirring, and after stirring for 2 hours, the stirring speed is 200 rpm, and the stirring temperature is 80±5°C, a preliminary mixture is obtained, and the -NCO groups in the preliminary mixture are fully reacted to form a polyurethane prepolymer; the second step: gradually adding modified acrylate monomers to the preliminary mixture, and then stirring for 1 hour, the stirring speed is 300 rpm, and the stirring temperature is 70±5°C. At this time, the acrylate monomers are grafted onto the polyurethane chain to form an acrylic modified polyurethane prepolymer; the third step: gradually adding a chain extender to the acrylic modified polyurethane prepolymer, and stirring The chain extension mixture is obtained after stirring for 30 minutes, the stirring speed is 300 rpm, and the stirring temperature is 50±5°C. After no obvious gel or particle precipitation in the chain extension mixture, deionized water is added for stirring, the stirring time is 30 minutes, the stirring speed is 400 rpm, and the stirring temperature is 50±5°C. After the mixture of the chain extension mixture and the deionized water is milky white or translucent uniform emulsion and no obvious stratification or large particles are present, a preliminary emulsion is obtained; the fourth step: after the preliminary emulsion is cooled to room temperature, an auxiliary agent is added for stirring, the stirring time is 15 minutes, the stirring speed is 300 rpm, and after the stirring is completed, triethylamine is added to adjust the pH value of the preliminary emulsion and the auxiliary agent mixture to 7-8 to obtain an acrylic acid modified waterborne polyurethane adhesive; The theoretical viscosity calculation formula of acrylic modified waterborne polyurethane adhesive is: Where: is the viscosity of acrylic modified waterborne polyurethane adhesive; is an empirical constant; is the density of acrylic modified waterborne polyurethane adhesive; is the glass transition temperature of acrylic acid modified waterborne polyurethane adhesive; is the operating temperature; is the average molecular weight of the acrylic acid modified waterborne polyurethane adhesive; the fluorescent adhesive is obtained according to the following steps: the fluorescent powder and the acrylic acid modified waterborne polyurethane adhesive are stirred and mixed, the stirring time is 15 minutes, and the stirring speed is 400 rpm.
[0031] Obtaining the actual viscosity of acrylic modified waterborne polyurethane adhesive , and compare and , determine whether the water content of the acrylic modified waterborne polyurethane adhesive needs to be increased or decreased. If the actual viscosity of the acrylic modified waterborne polyurethane adhesive is Greater than the theoretical viscosity of acrylic modified waterborne polyurethane adhesive Then add deionized water to dilute it and reduce the viscosity. On the contrary, if the actual viscosity of the acrylic modified waterborne polyurethane adhesive is obtained Less than the theoretical viscosity of acrylic modified waterborne polyurethane adhesive Continue stirring to reduce the water content and increase the viscosity; the viscosity of the prepared acrylic modified waterborne polyurethane adhesive is related to the polymer chain length, molecular weight and water content.
[0032] The long polymer chain, large molecular weight and low water content in the acrylic modified water-based polyurethane adhesive are the reasons for the excessive viscosity of the acrylic modified water-based polyurethane adhesive, while the low viscosity of the acrylic modified water-based polyurethane adhesive is due to the short polymer chain and the weak interaction between molecules, which leads to lower viscosity, and the higher water content will also reduce its viscosity; the theoretical viscosity and actual viscosity of the acrylic modified water-based polyurethane adhesive can be directly affected by controlling the molecular weight of the polymer. A larger molecular weight usually leads to a higher viscosity, and vice versa. At the same time, the water content of the acrylic modified water-based polyurethane adhesive also has a significant effect on its viscosity. Increasing the water content can dilute the polymer and reduce the viscosity, while reducing the content will increase the viscosity.
[0033] The acrylic modified waterborne polyurethane adhesive prepared by the above method has the characteristic of high viscosity. The introduction of acrylate significantly improves the polarity and intermolecular force of the acrylic modified waterborne polyurethane adhesive and increases the affinity of the molecular chain. The high molecular weight polyurethane matrix further enhances the adhesion through the flexible regulation of the chain segments. At the same time, the acrylic modified polyurethane with high cross-linking density in the acrylic modified waterborne polyurethane adhesive forms a highly brittle network structure after curing, which makes the cured acrylic modified waterborne polyurethane adhesive easy to break.
[0034] Specifically, in the above preparation process, the -NCO content in the preliminary mixture is monitored by a titratable method to ensure complete reaction; and infrared spectroscopy is used to confirm that the -OH group is reduced and acrylic acid grafting is completed, thereby ensuring the formation of acrylic acid-modified polyurethane prepolymer.
[0035] The aromatic polyester polyol can be any one of poly(trimethylene terephthalate), polyethylene phthalate and polyethylene adipate terephthalate; the aliphatic isocyanate can be any one of isophorone diisocyanate, hexamethylene diisocyanate and tetramethylene diisocyanate; the modified acrylate monomer can be any one of hydroxyethyl acrylate, hydroxypropyl methacrylate and butyl methacrylate; the auxiliary agent includes a stabilizer, a tackifier and an antioxidant; the modified acrylate monomer is used in the preparation of the aromatic polyester The proportions of polyols, aliphatic isocyanates, modified acrylate monomers, modified acrylate monomers, deionized water, chain extenders and additives are 40%~50%, 20%~25%, 10%~15%, 15%~20%, 0.5%~1.5% and 5%~10% respectively; among them, additives include stabilizers, tackifiers and antioxidants; the proportion of stabilizers is 0.1%~0.5%, the proportion of tackifiers is 1%~5%, and the proportion of antioxidants is 0.1%~0.3%.
[0036] Preferably, the proportion of polyethylene phthalate is 45%, the proportion of isophorone diisocyanate is 22%, the proportion of hydroxyethyl acrylate is 12%, the proportion of deionized water is 16%, the proportion of chain extender is 1%, the proportion of tackifier is 3%, the proportion of stabilizer is 0.3%, and the proportion of antioxidant is 0.2%.
[0037] Furthermore, the proportions of fluorescent powder and acrylic modified waterborne polyurethane adhesive in the fluorescent adhesive are 8%~13% and 87%~92%, respectively.
[0038] Preferably, the proportions of fluorescent powder and acrylic modified waterborne polyurethane adhesive in the fluorescent adhesive are 10% and 90% respectively; the fluorescent powder is zinc silicate-based fluorescent powder, and the diameter of the fluorescent powder particles is 1~2μm, specifically 1.5μm; the zinc silicate-based fluorescent powder has an efficient response to 365nm wavelength ultraviolet light, high luminous intensity, and strong weather resistance. After being irradiated with ultraviolet light, it has a good imaging effect. At the same time, the 10% fluorescent powder can provide enough luminescent particles to ensure the imaging effect without affecting the fluidity and bonding properties of the fluorescent adhesive, and the fluorescent powder particles with medium particle diameter can also take into account both fluorescence intensity and uniform distribution.
[0039] The initial substrate is obtained according to the following steps: the first step: preparing a coating mold 1 with a micro-concave structure, and coating a release layer coating on the coating mold 1, so that the release layer coating covers the micro-concave structure, wherein a plurality of equally spaced square grooves 11 are provided on the coating mold 1 corresponding to its rubbing surface 12, and two adjacent square grooves 11 are enclosed to form a micro-concave structure; the second step: coating the fluorescent adhesive on the coating mold 1, and allowing the fluorescent adhesive to fill the micro-concave structure; the third step: uniformly rubbing the fluorescent adhesive on the glassine paper through the coating mold 1, the release layer coating can allow the fluorescent adhesive to be completely transferred from the micro-concave structure to the glassine paper, and after the coating is completed, the glassine paper is subjected to six-stage thermal curing, and after the fluorescent adhesive forms an adhesive layer 2 on the glassine paper, the initial substrate is finally obtained, wherein, as Figure 6-Figure 7 As shown, a protrusion 22 is formed on the adhesive surface 21 of the adhesive layer 2 on the initial substrate corresponding to the square groove 11 .
[0040] By setting the depth, width and spacing of the micro-concave structure on the coating mold 1, the adhesive layer 2 after the fluorescent adhesive is cured can form a relatively strong adhesive effect on the surface of the product, so that when the label is peeled off the surface of the product, the residual amount of the adhesive layer 2 is significantly increased compared with ordinary labels. When the adhesive layer 2 remaining on the product is increased, the fluorescent display effect can be more obvious when irradiated with ultraviolet light in the future, thereby improving the anti-counterfeiting effect.
[0041] It should be noted that, by performing micro-concave coating, tiny bumps 22 can be formed on the adhesive surface of the adhesive layer 2. The tiny bumps 22 increase the contact area between the adhesive layer 2 and the surface of the product. When the label is peeled off from the surface of the product, the roughness and microstructure of the surface of the product will also interact with the bumps 22 on the adhesive layer 2. The rough surface of the product will produce a stronger adhesion with the adhesive layer 2. Therefore, when peeling, more adhesive layer 2 will remain on the surface of the product.
[0042] Furthermore, the depth of the square groove 11 is 20-30 μm, the width is 50-100 μm, the distance between two adjacent square grooves 11 is 100-150 μm, and the coating thickness of the fluorescent adhesive is 25±5 μm.
[0043] Preferably, the square groove 11 has a depth of 25 μm and a width of 80 μm, and the spacing between two adjacent square grooves 11 is 100 μm; the coating thickness of the fluorescent adhesive is 25 μm; after the fluorescent adhesive is coated and cured, a bump 22 is formed on the adhesive layer 2, which is printed by the square groove 11; the bump 22 includes 8000 to 9000 fluorescent powder particles, which ensures the imaging effect of the residual adhesive layer 2. At the same time, the square groove 11 with a moderate depth can accommodate enough glue to ensure the imaging effect. The wider square groove 11 increases the glue area and increases the residual amount. The smaller spacing can cover a larger area and enhance the imaging effect.
[0044] Furthermore, the six curing temperatures of the six-stage thermal curing are 75±5°C, 85±5°C, 95±5°C, 115±5°C, 110±5°C, and 90±5°C respectively; the six curing times of the six-stage thermal curing are 5-10 minutes, 10-15 minutes, 10-20 minutes, 5-10 minutes, 5-10 minutes, and 10-15 minutes respectively.
[0045] Specifically, the first curing time is 5 to 10 minutes. During this curing process, the low temperature is maintained to avoid too fast cross-linking of the fluorescent adhesive; the second curing time is 10 to 15 minutes. Through the second curing, the curing reaction is further enhanced, and the cross-linking structure is gradually established. The cross-linking density begins to increase, but it remains moderate to ensure that a certain microscopic uneven distribution can be formed inside the adhesive layer 2; the third curing time is 10 to 20 minutes. During this curing process, the curing temperature is close to the optimal curing temperature of the fluorescent adhesive, further strengthening the cross-linking. During this curing process, the cross-linking density is significantly increased, and by controlling the curing time of the curing process, the cross-linking density is avoided from being too high; the fourth curing time is 5 to 10 minutes. In the fourth curing, the curing temperature reaches the maximum curing temperature, the fluorescent adhesive is fully cured, and gradually An adhesive layer 2 is formed, and a certain internal stress is introduced into the adhesive layer 2. The fourth stage of curing, through high-temperature curing, will cause microcracks or internal stress to be generated inside the gradually formed adhesive layer 2 due to thermal expansion. The generated microcracks or internal stress will reduce the overall toughness of the adhesive layer 2, making it easier to break; the fifth stage of curing time is 5 to 10 minutes. Through the fifth stage of curing, the formed adhesive layer 2 can be slightly cooled to slow down the cross-linking speed and stabilize the internal structure of the curing. The fifth stage of curing can further improve the curing by maintaining high temperature for a short time, and at the same time form a certain thermal history effect; the sixth stage of curing time is 10 to 15 minutes. Through the sixth stage of curing, the formed adhesive layer 2 can be cooled down and cooled slowly to avoid excessive internal stress concentration caused by too fast cooling, and finally form an adhesive layer 2. At the same time, the cross-linking density in the adhesive layer 2 is moderate and some weak stress concentration points remain inside.
[0046] It should be noted that by making the adhesive layer 2 harder and more brittle through a higher cross-linking density, and by gradually increasing the temperature and controlling the time of each stage, an uneven cross-linking network can be formed in the adhesive layer 2. This unevenness may cause the adhesive layer 2 to be more easily broken under the action of external force. At the same time, during the high-temperature curing in the fourth stage, the adhesive layer 2 will introduce certain residual stress due to thermal expansion. In the subsequent cooling process in the fifth and sixth stages, the stress is not completely released, forming potential instability points inside the adhesive layer 2. These stress concentration points can reduce the overall strength of the adhesive layer 2, making it more likely to break. The stress remaining in the adhesive layer 2 and the higher cross-linking density can make the label more likely to break when it is peeled off the product, thereby increasing the adhesive layer 2 remaining on the product.
[0047] Embodiment 3: Basic content embodiment 1, the difference is: See also Figure 6-Figure 7 The final substrate in this embodiment is obtained according to the following steps: the first step: coating a white curing liquid composed of a modified acrylic ester liquid and a white pigment on the adhesive layer 2 on the initial substrate, and then thermally curing the white curing liquid. After the white curing liquid is cured, a white cured layer is formed on the adhesive layer 2; the second step: coating a black curing liquid composed of a modified acrylic ester liquid and a black pigment on the white cured layer, and then thermally curing the black curing liquid. After the black curing liquid is cured to form a black cured layer, the final substrate is obtained.
[0048] The complete label is obtained according to the following steps: the first step: coating an invisible mark forming liquid composed of a modified acrylic ester liquid and a fluorescent powder on an invisible mark mold, and transferring the invisible mark forming liquid to the surface of a final substrate by the invisible mark mold, and then curing the invisible mark forming liquid on the surface of the final substrate by thermal curing to form an invisible mark layer; the second step: coating the modified acrylic ester liquid on the invisible mark layer, and then curing it by thermal curing, and obtaining a complete label when a transparent cured layer is formed on the invisible mark layer.
[0049] Specifically, the invisible mark layer is arranged on the black solidified layer and is sealed by the transparent solidified layer. The black solidified layer can make the invisible mark layer have better imaging effect when it is displayed. The transparent solidified layer can effectively protect the invisible mark and the mark etched on the black solidified layer. Its high transparency and glossiness can not only make the complete label brighter and clearer in visual effect, but also improve the display effect of the invisible mark. It also has good UV resistance and can effectively resist ultraviolet radiation in sunlight, avoiding fading, aging or damage of the complete label and the invisible mark layer outdoors or exposed to sunlight for a long time.
[0050] Furthermore, the invisible marking forming liquid is prepared by mixing modified acrylate and fluorescent powder, the mixing time is 10 to 20 minutes, and the stirring speed is 200 to 600 rpm; the proportions of modified acrylate and fluorescent powder in the invisible marking forming liquid are 92% to 87% and 8% to 13%, respectively.
[0051] Embodiment 4: Basic content embodiment 1, the difference is: A multiple anti-counterfeiting flexible label in this embodiment is prepared by the method of Example 1. The multiple anti-counterfeiting flexible label includes glassine paper, glue layer 2, white solidified layer, black solidified layer, invisible identification layer, and transparent solidified layer connected in sequence from bottom to top.
[0052] When in use, peel off the glassine paper and stick the label to the product through the adhesive layer 2. The pasted label is marked with a laser-etched mark for basic identification, and the invisible identification layer provided can give the label an anti-counterfeiting function. After the label is peeled off from the product, the adhesive layer 2 remaining on the product can be developed after being irradiated with ultraviolet light to perform secondary anti-counterfeiting work, thereby improving the anti-counterfeiting effect of the label and solving the defect that the product lacks the anti-counterfeiting function after the label is peeled off from the product. After cleaning off the residual adhesive layer 2 on the product, the adhered area is irradiated with ultraviolet light, and the adhered area will also be developed, thereby further improving the anti-counterfeiting function of the label.
[0053] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a multiple anti-counterfeiting flexible label, characterized in that: The following steps are involved: S1, mixing aromatic polyester polyol, aliphatic isocyanate, modified acrylate monomer and additives to obtain acrylic acid modified waterborne polyurethane adhesive, and then adding fluorescent powder to mix to obtain fluorescent adhesive; S2, applying the obtained fluorescent adhesive micro-concave onto glassine paper and curing it to form an adhesive layer (2), thereby obtaining an initial substrate; S3, preparing a white curing liquid and a black curing liquid, first coating the white curing liquid on the initial substrate for curing, then coating the black curing liquid, and after curing, obtaining a final substrate; S4, preparing invisible mark forming liquid, first curing the invisible mark forming liquid on the final substrate, and then coating the modified acrylate liquid, and obtaining a complete label after curing.
2. The method for preparing a multiple anti-counterfeiting flexible label according to claim 1, characterized in that: The acrylic acid modified waterborne polyurethane adhesive is obtained according to the following steps: Step 1: Adding aromatic polyester polyol and aliphatic isocyanate into a reaction kettle for stirring, after stirring for 2 hours, at a stirring speed of 200 rpm and a stirring temperature of 80±5°C, a preliminary mixture is obtained, and the -NCO groups in the preliminary mixture are fully reacted to form a polyurethane prepolymer; Step 2: gradually add modified acrylate monomer to the preliminary mixture, and then stir for 1 hour at a stirring speed of 300 rpm and a stirring temperature of 70±5°C, at which time the acrylate monomer is grafted onto the polyurethane chain to form an acrylic modified polyurethane prepolymer; Step 3: gradually adding a chain extender to the acrylic modified polyurethane prepolymer, and stirring for 30 minutes, at a stirring speed of 300 rpm and a stirring temperature of 50±5°C to obtain a chain extension mixture, and after no obvious gel or particle precipitation in the chain extension mixture, adding deionized water for stirring, stirring for 30 minutes, at a stirring speed of 400 rpm and a stirring temperature of 50±5°C, and after the mixture of the chain extension mixture and the deionized water is a milky white or translucent uniform emulsion, and no obvious stratification or large particles exist, a preliminary emulsion is obtained; Step 4: After the preliminary emulsion is cooled to room temperature, an auxiliary agent is added and stirred for 15 minutes at a stirring speed of 300 rpm. After the stirring is completed, triethylamine is added to adjust the pH value of the mixture of the preliminary emulsion and the auxiliary agent to 7-8 to obtain an acrylic acid-modified waterborne polyurethane adhesive; The theoretical viscosity calculation formula of the acrylic acid modified waterborne polyurethane adhesive is: Where: is the viscosity of acrylic modified waterborne polyurethane adhesive; is an empirical constant; is the density of acrylic modified waterborne polyurethane adhesive; is the glass transition temperature of acrylic acid modified waterborne polyurethane adhesive; is the operating temperature; is the average molecular weight of acrylic acid modified waterborne polyurethane adhesive; The fluorescent adhesive is obtained according to the following steps: The fluorescent powder and the acrylic modified waterborne polyurethane adhesive were stirred and mixed for 15 minutes at a stirring speed of 400 rpm; Obtaining the actual viscosity of the acrylic modified waterborne polyurethane adhesive , and compare and , determine whether the water content of the acrylic modified waterborne polyurethane adhesive needs to be increased or decreased. If the actual viscosity of the acrylic modified waterborne polyurethane adhesive is Greater than the theoretical viscosity of acrylic modified waterborne polyurethane adhesive Then add deionized water to dilute it and reduce the viscosity. On the contrary, if the actual viscosity of the acrylic modified waterborne polyurethane adhesive is obtained Less than the theoretical viscosity of acrylic modified waterborne polyurethane adhesive Continue stirring to reduce the water content and increase the viscosity.
3. The method for preparing a multiple anti-counterfeiting flexible label according to claim 2, characterized in that: The aromatic polyester polyol may be any one of polytrimethylene terephthalate, polyethylene terephthalate, and polyethylene adipate terephthalate; The aliphatic isocyanate may be any one of isophorone diisocyanate, hexamethylene diisocyanate, and tetramethylene diisocyanate; The modified acrylate monomer may be any one of hydroxyethyl acrylate, hydroxypropyl methacrylate, and butyl methacrylate; The auxiliary agents include stabilizers, tackifiers and antioxidants.
4. The method for preparing a multiple anti-counterfeiting flexible label according to claim 3, characterized in that: In the preparation of the modified acrylate monomer, the proportions of aromatic polyester polyol, aliphatic isocyanate, modified acrylate monomer, modified acrylate monomer, deionized water, chain extender and auxiliary agent are 40% to 50%, 20% to 25%, 10% to 15%, 15% to 20%, 0.5% to 1.5% and 5% to 10% respectively; Among them, the additives include stabilizers, tackifiers and antioxidants; The proportion of stabilizers is 0.1%~0.5%, the proportion of tackifiers is 1%~5%, and the proportion of antioxidants is 0.1%~0.3%; The fluorescent powder and acrylic modified waterborne polyurethane adhesive account for 8% to 13% and 87% to 92% of the fluorescent adhesive, respectively.
5. The method for preparing a multiple anti-counterfeiting flexible label according to claim 1, characterized in that: The initial substrate is obtained according to the following steps: The first step is to prepare a coating mold (1) having a micro-concave structure, and to coat a release layer coating on the coating mold (1) so that the release layer coating covers the micro-concave structure, wherein the coating mold (1) is provided with a plurality of square grooves (11) at equal intervals corresponding to its rubbing surface (12), and two adjacent square grooves (11) enclose one micro-concave structure; Step 2: Apply the fluorescent adhesive onto the coating mold (1) and allow the fluorescent adhesive to fill the micro-concave structure; Step 3: The fluorescent adhesive is evenly printed on the glassine paper through a coating mold (1); the release layer coating allows the fluorescent adhesive to be completely transferred from the micro-concave structure to the glassine paper; after the coating is completed, the glassine paper is subjected to six-stage heat curing; after the fluorescent adhesive forms an adhesive layer (2) on the glassine paper, an initial substrate is finally obtained, wherein a protrusion (22) is formed on the adhesive surface (21) of the adhesive layer (2) on the initial substrate corresponding to the square groove (11).
6. The method for preparing a multiple anti-counterfeiting flexible label according to claim 5, characterized in that: The depth of the square groove (11) is 20 to 30 μm, the width is 50 to 100 μm, and the distance between two adjacent square grooves (11) is 100 to 150 μm; The coating thickness of the fluorescent adhesive is 25±5 μm; The six curing temperatures of the six-stage thermal curing are 75±5°C, 85±5°C, 95±5°C, 115±5°C, 110±5°C, and 90±5°C, respectively; the six curing times of the six-stage thermal curing are 5-10 minutes, 10-15 minutes, 10-20 minutes, 5-10 minutes, 5-10 minutes, and 10-15 minutes, respectively.
7. The method for preparing a multiple anti-counterfeiting flexible label according to claim 1, characterized in that: The final substrate is obtained according to the following steps: The first step is to apply a white curing liquid composed of a modified acrylic ester liquid and a white pigment on the adhesive layer (2) on the initial substrate, and then thermally cure the white curing liquid to form a white cured layer on the adhesive layer (2) after the white curing liquid is cured; Step 2: coating a black curing liquid composed of a modified acrylic ester liquid and a black pigment on the white curing layer, and then thermally curing the black curing liquid. After the black curing liquid is cured to form a black curing layer, the final substrate is obtained.
8. The method for preparing a multiple anti-counterfeiting flexible label according to claim 1, characterized in that: The complete label is obtained according to the following steps: The first step: coating the invisible logo forming liquid composed of modified acrylic ester liquid and fluorescent powder on the invisible logo mold, and transferring the invisible logo forming liquid to the surface of the final substrate through the invisible logo mold, and then curing the invisible logo forming liquid on the surface of the final substrate through thermal curing to form an invisible logo layer; Step 2: Apply the modified acrylic ester liquid on the invisible logo layer, and then cure it by heat curing. When a transparent cured layer is formed on the invisible logo layer, a complete label is obtained.
9. The method for preparing a multiple anti-counterfeiting flexible label according to claim 8, characterized in that: The invisible mark forming liquid is prepared by mixing modified acrylic ester liquid and fluorescent powder, the mixing time is 10 to 20 minutes, and the stirring speed is 200 to 600 rpm; Among them, the proportions of modified acrylate liquid and fluorescent powder in the invisible marking forming liquid are 92% to 87% and 8% to 13% respectively.
10. A multiple anti-counterfeiting flexible label, characterized in that: The multi-layer anti-counterfeiting flexible label is manufactured by the method according to any one of claims 1 to 9, comprising glassine paper, a glue layer (2), a white solidified layer, a black solidified layer, an invisible identification layer, and a transparent solidified layer connected in sequence from bottom to top.
Citation Information
Patent Citations
Production technology for adhesive for aluminum alloy plate flocking and special-purpose device
CN103626929A
Polyurethane adhesive, preparation method of polyurethane adhesive, aluminum-plastic film and preparation method of aluminum-plastic film
CN115975578A
Solvent-free polyurethane-based adhesive and preparation method thereof
CN116042160A
Anti-fake adhesive tape combining fluorescent anti-fake technology and laser holographic technology and manufacturing method of anti-fake adhesive tape
CN118834624A
Laser engraving label with white fragile film
CN222213600U